2021
DOI: 10.1123/ijsnem.2020-0287
|View full text |Cite
|
Sign up to set email alerts
|

Quality Control of Protein Supplements: A Review

Abstract: The growing consumer awareness regarding health and fitness has been leading to a huge rise in the consumption of nutritional supplements and, consequently, to an increase in concerns about their quality. In this sense, one of the most consumed products is protein supplements and, despite being safer than other types of supplements, there are several studies showing incompatibilities between what is present on the labels and their actual content. Therefore, this review is focused on gathering information about… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 96 publications
0
7
0
Order By: Relevance
“…The amount of TAA, expressed as g/100 g product, did not always correspond to the protein content reported in Table 1 . An incomplete recovery was expected considering the partial degradation of some amino acids (e.g., Trp, Tyr) during acid hydrolysis and the partial loss of Lys due to the irreversible glycosylation during product manufacturing and storage [ 4 ]. Gasparini et al [ 11 ] also reported a recovery of TAA after acid hydrolysis of WPC that was 25% lower than the protein content determined by the Kjeldahl method.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The amount of TAA, expressed as g/100 g product, did not always correspond to the protein content reported in Table 1 . An incomplete recovery was expected considering the partial degradation of some amino acids (e.g., Trp, Tyr) during acid hydrolysis and the partial loss of Lys due to the irreversible glycosylation during product manufacturing and storage [ 4 ]. Gasparini et al [ 11 ] also reported a recovery of TAA after acid hydrolysis of WPC that was 25% lower than the protein content determined by the Kjeldahl method.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, the literature in this research area is increasing as well, and the derived scientific knowledge is constantly evolving [ 2 , 3 ]. Sports supplements are basically nutrient-dense foods, with milk protein representing the main component [ 4 ]. Minor ingredients are vitamins, minerals, essential fatty acids, selected amino acids, fiber, among others.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we encourage future studies to investigate the presence of undeclared stimulants in energy drinks. Even though many related studies regarding the presence of prohibited substances in nutritional supplements exist, [22][23][24][25] there is still this gap in the literature for energy drinks.…”
Section: Resultsmentioning
confidence: 99%
“…14,15 Unfortunately, there are very few papers regarding the mineral content in these supplements and when they appear, they focus on heavy metals. [14][15][16] Generally, to assess the elemental content of selected metals in the above-mentioned supplements, graphite furnace atomic absorption spectrometry (GF-AAS), inductively coupled plasma optical emission spectrometry (ICP-OES) and inductively coupled plasma mass spectrometry (ICP-MS) are applied. 14 Nevertheless, the analysis performed using the above-mentioned instruments may be challenging due to certain issues related to their practical application.…”
Section: Introductionmentioning
confidence: 99%